HISTORICAL STAGES AND CONTENT OF AGRARIAN REFORMS IN UZBEKISTAN - Davlatbek Musaev (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, during the years of independence, various methods of ownership and the implementation of new forms of economic management in the agricultural sector of Uzbekistan were studied from a historical point of view. Also, in the research, the issues of the reforms and measures being taken to ensure economic growth, the strengthening of the environment of free competition in the context of marketing and market relations in the development of the farm were analyzed.